Simulation Metamodelling of Manufacturing Processes - Palajova, Silvia; Gregor, Milan (Communications - Scientific letters of the University of Zilina, 2011)
This paper deals with models going out of simulation models, so called metamodels. They represent one of the possible ways how to increase effectiveness of simulation optimization, how to reduce the requirements of time-consuming simulation of manufacturing systems and how to make simulation cheaper. The heart of the paper describes steps of a metamodel making process and approximation of a real data using regression analysis and least square method.